The Moloney Murine Leukemia Virus Repressor Binding Site Represses Expression in Murine and Human Hematopoietic Stem Cells - Haas, Dennis L. (American Society for Microbiology, 2003)
The Moloney murine leukemia virus (MLV) repressor binding site (RBS) is a major determinant of restricted expression of MLV in undifferentiated mouse embryonic stem (ES) cells and mouse embryonal carcinoma (EC) lines. We show here that the RBS repressed expression when placed outside of its normal MLV genome context in a self-inactivating (SIN) lentiviral vector. In the lentiviral vector genome context, the RBS repressed expression of a modified MLV long terminal repeat (MNDU3) promoter, a simian virus 40 promoter, and three cellular promoters: ubiquitin C, mPGK, and hEF-1a. In addition to repressing expression in undifferentiated ES and EC cell lines, we show that the RBS substantially repressed expression in primary mouse embryonic fibroblasts, primary mouse bone marrow stromal cells, whole mouse bone marrow and its differentiated progeny after bone marrow transplant, and several mouse hematopoietic cell lines. Using an electrophoretic mobility shift assay, we show that binding factor A, the trans-acting factor proposed to convey repression by its interaction with the RBS, is present in the nuclear extracts of all mouse cells we analyzed where expression was repressed by the RBS. In addition, we show that the RBS partially repressed expression in the human hematopoietic cell line DU.528 and primary human CD34(+) CD38(−) hematopoietic cells isolated from umbilical cord blood. These findings suggest that retroviral vectors carrying the RBS are subjected to high rates of repression in murine and human cells and that MLV vectors with primer binding site substitutions that remove the RBS may yield more-effective gene expression.